Commercial banking : the management of risk - Gup, Benton E.; Kolari, James W.; Fraser, Donald R. (Hoboken, NJ : J. Wiley, 2005)
This up-to-date text provides a comprehensive, practical introduction to bank management and current banking practices used to control different kinds of risk.
Rev. ed. of: Commercial banking / Donald R. Fraser. c2001.
Includes bibliographical references and indexes.
rua 24/07/13
loans
Keywords: Bank management; Risk management